2019
DOI: 10.3390/molecules24152714
|View full text |Cite
|
Sign up to set email alerts
|

A New Heterogeneous Catalyst Obtained via Supramolecular Decoration of Graphene with a Pd2+ Azamacrocyclic Complex

Abstract: A new G-(H2L)-Pd heterogeneous catalyst has been prepared via a self-assembly process consisting in the spontaneous adsorption, in water at room temperature, of a macrocyclic H2L ligand on graphene (G) (G + H2L = G-(H2L)), followed by decoration of the macrocycle with Pd2+ ions (G-(H2L) + Pd2+ = G-(H2L)-Pd) under the same mild conditions. This supramolecular approach is a sustainable (green) procedure that preserves the special characteristics of graphene and furnishes an efficient catalyst for the Cu-free Son… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(60 citation statements)
references
References 43 publications
9
51
0
Order By: Relevance
“…Partial characterization of graphene, G, has been done in a previous publication of the authors. 25 Additionally, the elemental composition of G after washing with water, obtained from the survey XPS, was 95.8% C, 0.3% S, and 3.9% O. Deconvolution into the components of C 1s and O 1s high-resolution XPS spectra was done to get insight into the nature of the oxygen functions. To carry this out, both the corresponding background literature and the accuracy of XPS measurements (± 0.2 eV) were taken into account.…”
Section: Resultsmentioning
confidence: 99%
“…Partial characterization of graphene, G, has been done in a previous publication of the authors. 25 Additionally, the elemental composition of G after washing with water, obtained from the survey XPS, was 95.8% C, 0.3% S, and 3.9% O. Deconvolution into the components of C 1s and O 1s high-resolution XPS spectra was done to get insight into the nature of the oxygen functions. To carry this out, both the corresponding background literature and the accuracy of XPS measurements (± 0.2 eV) were taken into account.…”
Section: Resultsmentioning
confidence: 99%
“…It was later in the spotlight for its ability to form metal complexes [6][7][8], but its wider success was achieved thanks to its utilisation as a scaffold for the preparation of new materials that have proven effective in a variety of applications. Indeed, L derivatives decorated with different hanging functionalities have been studied for several biomedical (MRI contrast agents [9][10][11][12], antiproliferative treatments [13][14][15][16], radiotherapy [17,18], enzyme mimicking [19,20] and antioxidant activity [21][22][23]), chemosensing [24][25][26][27] and catalytic [28][29][30][31][32][33] applications. Very recently, (MRI contrast agents [9][10][11][12], antiproliferative treatments [13][14][15][16], radiotherapy [17,18], enzyme mimicking [19,20] and antioxidant activity [21][22][23]), chemosensing [24][25]…”
Section: Introductionmentioning
confidence: 99%
“…Anion-π interactions were also found to play an important role in the formation of highly organised polyiodide complexes [44,45] and iodide based permutable organised frameworks (POF) [46] with a pyridinium-based ligand such as Stoddart's blue box (BB, cyclobis(paraquat-p-phenylene)). (MRI contrast agents [9][10][11][12], antiproliferative treatments [13][14][15][16], radiotherapy [17,18], enzyme mimicking [19,20] and antioxidant activity [21][22][23]), chemosensing [24][25][26][27] and catalytic [28][29][30][31][32][33] applications. Very recently, it has been shown that L and its N-trimethylated derivative are capable of stabilising iodine-dense three-dimensional networks that might be relevant for crystal engineering purposes and the design of solid-state conductors [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scorpiand type aza-macrocyclic ligands, that is aza-macrocyclic ligands with coordinating tails [1], and their metal complexes have attracted considerable interest thanks to the numerous uses they have been tested for, including but not limited to various biomedical applications [2,3] (MRI contrast agents [4,5], radioisotopes complexation and radiolabelling [6][7][8][9], radiotherapy [10][11][12][13][14], chelation therapy [15][16][17], antiproliferative treatments [18][19][20][21], enzyme mimicking [22][23][24][25][26][27][28][29]), catalysis [30][31][32][33][34][35][36] and chemosensing [37][38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%